Sharia-Based Liquidity Management Strategy Amidst Market Dynamics: A Qualitative Study at Bank Muamalat Indonesia - Laili Norma Faseh; Moh Andrean Umami; Afifatus Zakiya; Ahmad Munir; Achmad Budi Susetyo (Values: Jurnal Kajian Islam Multidisiplin, 2026)
Funding in a company can be obtained from various investment sources, on of them by issuing Islamic bonds (Sukuk). The announcement of the issuance of sharia bonds can be used as one of the information considerations in investing for investors. This study aims to analyse the capital market reaction to the issuance of Islamic bonds. This study uses event study analysis which is used to determine abnormal returns around the issuance of Islamic bonds, to find out significant differences in average abnormal returns around Islamic bonds issuance and to find out significant differences in trading volume activity around Islamic bonds issuance. The population in this study are all announcements of issuance of sharia bonds listed on the Indonesia Stock Exchange for the period 2009-2018 and then re-select companies listed on ISSI as of May 28, 2019. Event study with a window period of 21 days (t-10 to t+10). Sampling uses a purposive sampling criteria technique. Samples obtained were 55 Sukuk issuance which included 12 announcements of Islamic bonds issuance.